2019
DOI: 10.9734/jeai/2019/42305
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability Analysis for Quantitative Traits in Rice (Oryza sativa L.)

Abstract: The present study was conducted at Agricultural and Horticultural Research station, Kathalagere, Karnataka. The experiment consisted of sixty four rice genotypes that were evaluated to study genetic variability, heritability and genetic advance for grain yield along with four yield-associated traits. The experiment was conducted using 8x8 simple lattice square design during the 2015 kharif main cropping season. The analysis of variance revealed statistically significant differences (p<0.05) indicating the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…PCV and GCV were high for the traits viz., the number of panicles per square meter (10.01 %, 9.45 %), grain yield per plot and grain yield per hectare (9.24 %, 8.39 %), the plant height (6.97 %, 5.68 %), the days to 50% flowering (6.64 %, 6.46 %) and days to maturity (5.31% and 5.17%) (Table 2). The results found in this study are corroborated with the findings of Manjunath et al, Fathima et [11,12,13,14] for plant height and the panicles per square meter as well as days to maturity. For the grain yield per plot and grain yield per hectare in rice by Manjunatha B et al and Singh et al [15,16].…”
Section: Resultssupporting
confidence: 92%
“…PCV and GCV were high for the traits viz., the number of panicles per square meter (10.01 %, 9.45 %), grain yield per plot and grain yield per hectare (9.24 %, 8.39 %), the plant height (6.97 %, 5.68 %), the days to 50% flowering (6.64 %, 6.46 %) and days to maturity (5.31% and 5.17%) (Table 2). The results found in this study are corroborated with the findings of Manjunath et al, Fathima et [11,12,13,14] for plant height and the panicles per square meter as well as days to maturity. For the grain yield per plot and grain yield per hectare in rice by Manjunatha B et al and Singh et al [15,16].…”
Section: Resultssupporting
confidence: 92%
“…Padmaja et al, (2008) also reported high genetic advance for test weight, days to maturity, panicle weight, seeds per panicle, plant height, panicles per plant, flag leaf width, tillers per plant and flag leaf length. Manjunatha and Kumara (2019) also reported the high genetic advance for days number to 50 per cent flowering.…”
Section: Resultsmentioning
confidence: 93%
“…High heritability for test weight, days to maturity, panicle weight, seeds per panicle, plant height, panicles per plant, flag leaf width, tillers per plant, flag leaf length was also reported by Padmaja et al, (2008). Manjunatha and Kumara (2019) have also reported high heritability for day's number to 50 per cent flowering. Pal and Sabesan (2010) have also reported high heritability for internodal length, culm diameter, culm wall thickness and lodging per cent.…”
Section: Resultsmentioning
confidence: 98%
“…Early transplanting is the cultural practice aimed at exploiting favorable environmental conditions, which have the potential for resource utilization and significant improvement in yield [4]. However, the effectiveness of early transplanted rice highly depends on the genetic composition of the varieties, as different varieties respond differently in various environments [5][6][7].…”
Section: Introductionmentioning
confidence: 99%